Characteristics of potential head injury situations at the FIFA World Cup Qatar 2022 - Peek, K.; Aiello, F.; Avery, L.; Gardner, T.; Rutherford, H.; Massey, A.; Georgieva, J.; Andersen, T. E.; Dahlén, S.; Serner, A. (Science and Medicine in Football, 2026)
This exploratory video analysis study aimed to review characteristics of potential head injury situations during a men`s professional international football tournament. For 64 matches of the FIFA World Cup Qatar 2022™ FIFA analysts used match footage to record all potential head injury situations. A potential head injury situation was defined as a player staying down for more than 5 s and/or requesting medical attention, and where the body impact location included the player`s head. Characteristics were further recorded for match, player (i.e. player action including aerial duels), medical assessment, and outcome (e.g. substitution). Descriptive statistics are reported as well as Pearson`s Chi-squared test (or Fisher`s exact test) to explore potential head injury situations more likely to result in medical attention. In total, 149 potential head injury situations occurred in 56 matches (mean 2.33/match, range 0-6) involving 117 players. Eight matches resulted in no incidents. Aerial duels were the most frequent match characteristic leading to a potential head injury situation. Injury stoppage with on-pitch medical assessment occurred in 35 of the 149 potential head injury situations (23%), with pitch-side assessment also occurring in 15 situations (10%), resulting in four concussion substitutions. Players were more likely to require medical attention for potential head injuries sustained when the ball was loose (?2 = 6.88; p = 0.038) when the injured player was jumping (FET p = 0.044) and for head-to-head contact (FET p = <0.001). Further exploration of aerial duels during match play which do and do not lead to potential and actual head injuries is recommended.